APPLICATION OF CUSTOMER RELATIONSHIP MANAGEMENT ON A WEBSITE - Ardella, Cindy (Journal of Data Analytics, Information, and Computer Science, 2024)
Building material distribution is the business of PT. Kejora Inti Mas. The corporation engages in limited customer interaction and has a narrow target market since it adheres to traditional business methods. To build solid client relationships, broaden target markets, and boost competitiveness, businesses need websites that include a customer relationship management (CRM) strategy. PT. Kejora Inti Mas is implementing the CRM strategy by integrating various features such as live chat support, product recommendations, subscriber features, email notifications for order statuses, customer testimonials, rewards programs, live chat support, seamless integration with WhatsApp chats, and shipping cost calculation. The system is being developed using the Rapid Application Development (RAD) approach, which consists of three steps: system design, system implementation, and requirements planning. The system was implemented for a month before Keywords: Customer Relationship Management, Website, Rapid Application Development.